2020
DOI: 10.1016/j.aim.2020.107070
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing the Bost–Connes semigroup actions from K-theory

Abstract: We complete the classification of Bost-Connes systems. We show that two Bost-Connes C*-algebras for number fields are isomorphic if and only if the original semigroups actions are conjugate. Together with recent reconstruction results in number theory by Cornelissen-de Smit-Li-Marcolli-Smit, we conclude that two Bost-Connes C*-algebras are isomorphic if and only if the original number fields are isomorphic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(48 citation statements)
references
References 17 publications
1
47
0
Order By: Relevance
“…A general construction of full and reduced C * -algebras for left cancellative monoids was introduced by Li, [Li12], and soon fundamental questions about the interplay between nuclearity of the C * -algebra and amenability of the monoid or its left inverse hull were raised, see [Li13,Nor14]. Subsequent work on semigroup C *algebras that centered on computing K-theory revealed impressively rich connections to number theory, see [Li14,KT], and geometric group theory, see [ELR16].…”
Section: Introductionmentioning
confidence: 99%
“…A general construction of full and reduced C * -algebras for left cancellative monoids was introduced by Li, [Li12], and soon fundamental questions about the interplay between nuclearity of the C * -algebra and amenability of the monoid or its left inverse hull were raised, see [Li13,Nor14]. Subsequent work on semigroup C *algebras that centered on computing K-theory revealed impressively rich connections to number theory, see [Li14,KT], and geometric group theory, see [ELR16].…”
Section: Introductionmentioning
confidence: 99%
“…This construction of C*-algebras from number fields is one of the easiest and most natural. Our main result says that the rigidity phenomenon from [38,Corollary 1.2] holds even in this setting: Theorem 1.1. Let K and L be number fields.…”
mentioning
confidence: 88%
“…The Hecke C*algebras constructed from totally positive ax + b-groups in [42] are less ad hoc. These are full corners in the Bost-Connes C*-algebra by [41], so the results of the second-named author and Kubota in [38] yield a rigidity theorem for such Hecke C*-algebras. However, from the perspective of rigidity for C*-algebras constructed from number fields, there are other C*-algebras that are more natural from a number-theoretic or dynamical view point.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Recently, Takeishi used K-theoretical techniques inspired by [23] to prove that the C * -algebra in the Bost-Connes system associated to a number field K recovers the Dedekind zeta-function of K, [29], thus refining the findings of [18] that showed that the entire Bost-Connes system determines the Dedekind zetafunction. Finally, the full reconstruction of number fields up to isomorphism from the C * -algebras of the respective Bost-Connes systems has been recently achieved by Kubota and Takeishi [12], see also [6].…”
Section: Introductionmentioning
confidence: 99%